2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6942962
|View full text |Cite
|
Sign up to set email alerts
|

Prior-assisted propagation of spatial information for object search

Abstract: We propose a novel method for efficient object search in realistic environments. We formalize object search as a probabilistic inference problem over possible object locations. The method makes two contributions. First, we identify five priors, each capturing structure inherent to the physical world that is relevant to the search problem. Second, we propose a formalization of the object search problem that leverages these priors effectively. Our formalization in form of a probabilistic graphical model is capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Several researchers have leveraged the fact that our environments are rich with cues that can assist robots in various tasks that require reasoning about objects and their locations. For example, different works have addressed object classification, predicting the locations of objects using typical 3D structures in indoor environments or object-object relations such as co-occurrences in a scene (Aydemir and Jensfelt, 2012; Joho et al, 2011; Kunze et al, 2014; Lorbach et al, 2014; Nyga et al, 2014). However, our work is concerned with learning pairwise object preferences to compute preferred arrangements when tidying up.…”
Section: Related Workmentioning
confidence: 99%
“…Several researchers have leveraged the fact that our environments are rich with cues that can assist robots in various tasks that require reasoning about objects and their locations. For example, different works have addressed object classification, predicting the locations of objects using typical 3D structures in indoor environments or object-object relations such as co-occurrences in a scene (Aydemir and Jensfelt, 2012; Joho et al, 2011; Kunze et al, 2014; Lorbach et al, 2014; Nyga et al, 2014). However, our work is concerned with learning pairwise object preferences to compute preferred arrangements when tidying up.…”
Section: Related Workmentioning
confidence: 99%
“…Much subsequent work in robotics has expanded on this formulation; Aydemir et al [1] provides a good overview of the numerous works. Most of the later work attempt to capture additional structural information found in typical household environments, including object-location and object-object co-occurrences [8], [1], spatial relations [9], [11], object affordances [12] and scene ontologies [14]. While from these studies it is clear that additional knowledge is beneficial, most are focused on relatively uncluttered domains.…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that the refinement of the locations considered for search has a positive influence to search performance [15]. For example, object search based on the basis of Qualitative Spatial Relations is presented in [16], while five priors representing structure of the world and the specific scene are introduced and encoded into a probabilistic model and used to build consistent hypotheses about object locations in [17].…”
Section: Related Workmentioning
confidence: 99%